2019
DOI: 10.2147/dmso.s209436
|View full text |Cite|
|
Sign up to set email alerts
|

<p>2-dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione isolated from <em>Averrhoa carambola L</em>. root ameliorates diabetic nephropathy by inhibiting the TLR4/MyD88/NF-κB pathway</p>

Abstract: Background Averrhoa carambola L. is a traditional medicinal herb that has long been used to treat diabetes. Our previous studies found that 2-dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD) isolated from A. carambola L . roots could ameliorate diabetic nephropathy (DN), but its exact mechanism remains unclear. Methods A DN model was established by streptozotocin (STZ, 100 mg/kg body weight) in TLR4 knockout (TLR4-/-, KO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Accordingly, consumption of A. carambola has been demonstrated to boost immunity and help remove toxins from the body. In addition, A. carambola extracts exhibit anti-inflammatory and antiulcerogenic properties [13] and ameliorate nonalcoholic hepatic steatosis [14] and diabetic nephropathy [15]. Our previous study indicated that methanolic extract of A. carambola leaf (MEACL) demonstrated antihyperlipidemic and antioxidant effects in poloxamer-407-induced hyperlipidemic rat model that were comparable to that of atorvastatin [16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, consumption of A. carambola has been demonstrated to boost immunity and help remove toxins from the body. In addition, A. carambola extracts exhibit anti-inflammatory and antiulcerogenic properties [13] and ameliorate nonalcoholic hepatic steatosis [14] and diabetic nephropathy [15]. Our previous study indicated that methanolic extract of A. carambola leaf (MEACL) demonstrated antihyperlipidemic and antioxidant effects in poloxamer-407-induced hyperlipidemic rat model that were comparable to that of atorvastatin [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on A. cherimola have identified a-glucosidase inhibitor phenolamides from leaves [44], acetylcholinesterase inhibitor alkaloids from the fruit peel [48], anticancer acetogenins and cyclic peptides from seeds [33,41], and tyrosinase inhibitor proanthocyanidins from the fruit pericarp [52]. Studies on A. carambola have suggested versatile therapeutic uses of the compound DMDD from the root, including the treatment of diabetic kidney disease [113], metabolic syndrome [114], Alzheimer's disease [122], and breast cancer cells [125], and in addition an antihyperglycemic effect of apigenin-6-C-b-fucopyranoside from the leaves [115]. Concern for possible adverse effects point to nephrotoxic oxalic acid and neurotoxic caramboxin of A. carambola fruit [128,130], but these problems are uncommon and linked to high intake and kidney comorbidity, while no warning is issued for regular consumption by healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclohexanedione 2-Dodecyl-6methoxycyclohexa-2,5-diene-1,4-dione (DMDD) isolated from the root has been proved to lessen the hyperglycemia-stimulated, epithelial-mesenchymal transition, an initiating step of diabetic kidney disease, in a proximal tubule epithelial cell line [112]. In a streptozotocin-induced, diabetic nephropathy mouse model, DMDD has mitigated kidney damage and inflammation by inhibiting NF-kB activation induced by the TLR4/Myeloid Differentiation factor (Myd88) signaling pathway [113]. DMDD has also contrasted the obesity and insulin resistance induced in mice by a high-fat diet, by decreasing body and adipose tissue weights, glucose and lipid serum levels, as well as TLR4 and Myd88 expression in adipose tissue, and increasing insulin sensitivity [114].…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…12 Our previous works have revealed that the extract of Averrhoa carambola L. root had a high hypoglycemic activity on streptozotocin-induced diabetic mice. 13,14 The present research was projected to increase the hypoglycemic activity of BACR in diabetic animals. Figure 6 Pancreatic histological changes by HE staining (400×) (n=10).…”
Section: Discussionmentioning
confidence: 99%